(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the distinctive characteristics of interlanguage development among Uzbek and Russian speakers learning English. The research analyzes specific linguistic patterns, common errors, and developmental sequences that emerge during the acquisition process, highlighting how native language features influence second language production. By comparing interlanguage features across these language pairings, this study identifies key transfer phenomena, fossilization patterns, and pedagogical implications for language teaching in multilingual contexts.